"Brain training": Two Types of Approaches to Intervention, and Two Approaches to Evaluation - Dorothy Howie (Pensa MultiMedia, 2022)
This paper explores a 2016 paper published by Simons and colleagues on the efficacy of 'brain training' programs, in relation to the Feuerstein Instrumental Enrichment program for teaching thinking. It compares the focus of this Simons paper on interventions with commercial brain training software, with the broad Feuerstein intervention aimed at structural cognitive modifiability. Two approaches to evaluation are discussed. This paper suggests an alternative set of criteria for evaluating effectiveness to the "gold standard" traditional clinical experimental design criteria used in the Simons paper. This is the criteria put forward by Sternberg for evaluating intellectual skill training interventions. It applies these Sternberg criteria systematically to the review by Simons and colleagues and to the Feuerstein program, citing a wide range of research literature on the Feuerstein program.